Gen Z Consumer Behavior in Jakarta MRT Stations Retail Shop - Jessica Monik; Naomi Patadungan; Dicky Richard Haspri; Whisnu Whisnu (Syntax Corporation Indonesia, 2024)
This paper focuses on the shopping behavior of Gen Z consumers while shopping in Jakarta MRT station. MRT has become an alternative solution for transportations in Jakarta to get over traffic jam and tends to have punctual schedule. Each MRT stations have different type of brand and retail stores that varies from food and beverages, convenience store and others. Gen Z often use MRT as their preferred transportations and in this study their response towards MRT stations retail and shopping behavior was analyzed during a short interview with the respondents. Analysis in retail shop and how consumers behave towards shopping including their motivations and preferences. In applying a qualitative approach, the study brings forth the Gen Z passengers' preference for punctual, fast travel, brand loyalty, and quick shopping. The results from the research indicate that Gen Z consumers tend to shop at retail shops near the city transit stations in the morning, providing that they love speed and efficiency. It also shows that brand play key role in the Gen Z consuming behavior and how they have planned ahead before actually shopping. The research also indicates that retail firms need to blend the digital way of doing business and social responsibility in order to reach this popular demographic. The dynamics of Gen Z consumers contribute significantly to the choice of products, place, time, and retail shops. Through a deep understanding of these elements, a business can succeed in the trends of the consumers in the urban transit setting.